2017
DOI: 10.1038/srep40911
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Layer-by-Layer Growth of ZnO Nanopillar by In situ High Resolution Transmission Electron Microscopy

Abstract: Catalyst-free methods are important for the fabrication of pure nanowires (NWs). However, the growth mechanism remains elusive due to the lack of crucial information on the growth dynamics at atomic level. Here, the noncatalytic growth process of ZnO NWs is studied through in situ high resolution transmission electron microscopy. We observe the layer-by-layer growth of ZnO nanopillars along the polar [0001] direction under electron beam irradiation, while no growth is observed along the radial directions, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…This development has been accelerated by the advent of faster and more sensitive detectors such as the direct detection camera [1] ; but also by the development of the environmental TEM, where it becomes possible to study how, for example, nanoparticles respond to reaction gases in real time. Examples include characterizing the distribution of dopants [3] and defects, [4] in situ imaging of phase transformations, [5] structural reordering during materials growth, [6,7] dynamic surface phenomena, [8] and identification of chemical phases in nanoparticles. In many applications, accurate identification and classification of local DOI: 10.1002/adts.201800037 structure is a crucial first step in deriving useful information from atomic-resolution images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This development has been accelerated by the advent of faster and more sensitive detectors such as the direct detection camera [1] ; but also by the development of the environmental TEM, where it becomes possible to study how, for example, nanoparticles respond to reaction gases in real time. Examples include characterizing the distribution of dopants [3] and defects, [4] in situ imaging of phase transformations, [5] structural reordering during materials growth, [6,7] dynamic surface phenomena, [8] and identification of chemical phases in nanoparticles. In many applications, accurate identification and classification of local DOI: 10.1002/adts.201800037 structure is a crucial first step in deriving useful information from atomic-resolution images.…”
Section: Introductionmentioning
confidence: 99%
“…In many applications, accurate identification and classification of local structure is a crucial first step in deriving useful information from atomic‐resolution images. Examples include characterizing the distribution of dopants and defects, in situ imaging of phase transformations, structural reordering during materials growth, dynamic surface phenomena, and identification of chemical phases in nanoparticles …”
Section: Introductionmentioning
confidence: 99%
“…It can be used to visualize inorganic, organic, carbon-based, biological, and complex materials as spherical and equiaxial particles, tubes, flakes, rods, or fibers. The size, size distribution, crystalline structures, and aggregates of ZnO NPs have been analyzed using TEM [46,118,119]. The TEM technique is extensively used to determine the size, size distribution, and morphology of ZnO NPs based on the stabilizer (glycerol)-to-zinc source ratios during the synthesis [46,109].…”
Section: Physicochemical Characterization and Toolsmentioning
confidence: 99%
“…The TEM technique is extensively used to determine the size, size distribution, and morphology of ZnO NPs based on the stabilizer (glycerol)-to-zinc source ratios during the synthesis [46,109]. Li et al [118] reported the layer-by-layer growth of ZnO nanopillar crystals using in situ, high-resolution TEM. Ludi and Niederberger [119] also used TEM to demonstrate the nucleation and growth of ZnO NPs, including the hexagonal pyramid and oleic acid-stabilized, cone-shaped ZnO nanocrystals in liquid media.…”
Section: Physicochemical Characterization and Toolsmentioning
confidence: 99%
“…For the last two decades, ZnO nanostructures have garnered substantial attention because of their prodigious potential for blue and ultra-violet (UV) optoelectronic devices [1][2][3][4][5][6]. Among various nanostructures, 1-dimensional ZnO (e.g., nanorod [7,8], nanoneedle [9,10], nanopillar [11,12], etc.) is one of the most attractive nanoarchitectures due to its short pathway for carrier transport [13], high surface-to-volume ratio for photon collection [14], and low exciton-phonon coupling strength [15].…”
Section: Introductionmentioning
confidence: 99%